La didáctica de las lenguas: una disciplina en proceso de construcción - Dolz, Joaquim; Gagnon, Roxane; Mosquera, Santiago (Didáctica. Lengua y Literatura, 2009)
The last 30 years have shaped the Didactic of Languages as a disciplinary field. This contribution analyzes the social and institutional context that allowed the scientific development of studies on teaching and learning languages; this paper also discusses the finals goals for teaching and learning languages, focusing on the concept of plurilingualism. In order to present the field of the Didactic of Languages, we will underline some of its principal's researches; in the same time, we will highlight the scientific concepts that contribute to its theoretical formalization. The development of plurilingual and intercultural approach for improving the teaching and learning of languages is the key axis of this general panorama. En francés:Les trente dernières années ont vu l'émergence de la didactique des langues comme discipline scientifique. Cette contribution vise à définir cette nouvelle discipline. Pour ce faire, nous analyserons le contexte social et institutionnel qui a permis son développement scientifique. Nous discuterons aussi les finalités prioritaires de l'enseignement des langues, en portant une attention toute particulière sur le plurilinguisme. Enfin, nous présenterons l'évolution des principales recherches, mettant évidence les principaux concepts qui ont contribué à la formalisation théorique. Les questions en rapport avec le développement du plurilinguisme et l'enseignement intégré des langues seront les axes centraux de cette contribution.
Keywords: Languages education; Intercultural approach; First and Second languages; Plurilinguialism; Learning progression; Didactic transposition; Didactic system; Didactique des langues; Enseignement intégré des langues; Langue première et angue seconde